The Irish assassins conspiracy, revenge, and the Phoenix Park murders that stunned Victorian England - Kavanagh, Julie 1952- (Atlantic Monthly Press, 2021)
"One sunlit evening, May 6, 1882, Lord Frederick Cavendish and Thomas Burke, Chief Secretary and Undersecretary for Ireland, were ambushed and stabbed to death while strolling through Phoenix Park in Dublin. The murders were funded by American supporters of Irish independence and carried out by the Invincibles, a militant faction of republicans armed with specially-made surgeon's blades. They ended what should have been a turning point in Anglo-Irish relations. A new spirit of goodwill had been burgeoning between British Prime Minister William Gladstone and Ireland's leader Charles Stewart Parnell, with both men forging in secret a pact to achieve peace and independence in Ireland-with the newly appointed Cavendish, Gladstone's protégé, to play an instrumental role in helping to do so. The impact of the Phoenix Park murders was so cataclysmic that it destroyed the pact, almost brought down the government, and set in motion repercussions that would last long into the twentieth century. In a story that spans Donegal, Dublin, London, Paris, New York, Cannes, and Cape Town, Julie Kavanagh thrillingly traces the crucial events that came before and after the murders. From the adulterous affair that caused Parnell's downfall; to Queen Victoria's prurient obsession with the assassinations; and the investigation spearheaded by Superintendent John Mallon, also known as the "Irish Sherlock Holmes," culminating in the eventual betrayal and clandestine escape of leading Invincible James Carey and his murder on the high seas, The Irish Assassins brings us intimately into this fascinating story that shaped Irish politics and engulfed an Empire. This is an unputdownable book from one of our most "compulsively readable" (Guardian) writers"--
Keywords: Cavendish, Frederick Charles -- Lord -- 1836-1882; Burke, Thomas Henry -- 1829-1882; Irische Frage; Attentat; Phoenix Park -- Dublin; Burke, Thomas Henry / 1829-1882 / Assassination; Cavendish, Frederick Charles / Lord / 1836-1882 / Assassination; Irish National Invincibles; Phoenix Park Assassination, 1882; Assassination / Ireland / Dublin / History / 19th century; Irish question; Ireland / Politics and government / 1837-1901; Great Britain / Politics and government / 1837-1901; Ireland / Foreign relations / Great Britain; Great Britain / Foreign relations / Ireland; HISTORY / Europe / Ireland; Cavendish, Frederick; Assassination; Diplomatic relations; Politics and government; Great Britain; Ireland; 1837-1901; True crime stories